Recent Progress and Development of G-Quadruplex-Based Luminescent Assays for Ochratoxin A Detection - Nao, Sang-Cuo; Wu, Ke-Jia; Wang, Wanhe; Leung, Chung-Hang; Ma, Dik-Lung (Frontiers in Chemistry, 2020)
Ochratoxin A (OTA) is a mycotoxin that is widespread throughout the world. It contaminates foods such as vegetables, fruits, and rice. It harms human health and has potential carcinogenic effects. The G-quadruplex (G4) is a tetraplexed DNA structure generated from guanine-rich DNA that has found emerging use in aptamer-based sensing systems. This review outlines the status of OTA contamination and conventional detection methods for OTA. Various G4-based methods to detect OTA developed in recent years are summarized along with their advantages and disadvantages compared to existing approaches.